Dekadensi Kesantunan Berbahasa Mahasiswa Lintas Budaya di Universitas Tribhuwana Tunggadewi Malang: Kajian Antropososiopragmatik - Kamhar, Muhammad Yusi; Mulyono, Mulyono; Mintowati, Mintowati; Lestari, Erma (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research examines the phenomenon of the decadence of language politeness by focusing on changes in politeness values ​​and the decline in communication ethics. This research is based on Brown and Levinson's theory of politeness which pays attention to the factors of social distance, social power, and threat ratings in communication, as well as anthroposociopragmatic theory to understand the influence of culture and social structure on language use. The method used is descriptive qualitative, with data collection through direct observation and analysis of student digital communication documents, especially via WhatsApp. Data analysis shows that there is a decline in politeness in language which is characterized by the use of less polite speech, both in daily communication between students and with lecturers. The research results show that the decadence of language politeness among cross-cultural students at Universitas Tribhuwana Tunggadewi Malang is influenced by various factors, including environmental influences, social media, and a lack of understanding of language politeness norms in diverse socio-cultural contexts. This study emphasizes the importance of understanding intercultural communication, cultural identity, and social interaction in overcoming the decadence of language politeness, as well as the need to integrate material on language politeness in higher education to develop effective and polite student communicative competence.